(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background The study was done to compare and evaluate the effects of intrathecal fentanyl and midazolam as an adjuvant with hyperbaric bupivacaine. Material and methodsThis study was conducted on 90 adult female patients aged 18-35 years and ASA grade I/II undergoing elective or emergency caesarean section. The patients were randomly divided into three groups having 30 patients in each group.Group A received 1.5ml 0.5% Bupivacaine plus 0.5ml NS, Group B received 1.5ml 0.5% Bupivacaine with 0.5ml(25 mcg) Fentanyl, Group C received 1.5ml 0.5% Bupivacaine with 0.5ml (2.5 mg) Midazolam. Results There was no significant difference in the demographic data and surgical characteristics in the three groups.Regression to sensory level S2 was significantly prolonged in Group B(257.87±11.95 min) and Group C(252.87±8.66min) as compared to Group A(151.80±8.0min). However, the duration of motor blockade was comparable between Group A, Group B and Group C (P value>0.05). Duration of complete and effective analgesia was significantly prolonged in the Group B and Group C as compared to Group A (p<0.0001). ConclusionPresent study demonstrated that addition of fentanyl (25μg) and Midazolam (2.5 mg) to low dose bupivacaine (7.5 mg) intrathecally in patients undergoing caesarean section improves the quality of anaesthesia and post-operative analgesia with hemodynamic stability and without compromising neonatal outcome.